Foreign Competition and Domestic Industry Profitability - Esposito, Louis; Esposito, Frances Ferguson (The Review of Economics and Statistics, 1971)
R ECENT studies investigating the variability in inter-industry profit rates largely ignore the influence of actual and potential foreign competition [2, 5, 6, 15, 171. This paper examines the influence of foreign competition on industry profitability and concludes that such competition, as represented by the level of imports, appears to exert a significant and negative effect on industry profit rates. The evidence is consistent with the hypothesis that less restrictive trade policies encourage more competitive pricing behavior in domestic industries. Section I of this paper develops the analytical framework within which to view potential foreign competition. Section II describes the model and presents the major empirical results. Section III discusses the implications of the empirical results with respect to foreign trade policies.